Wybrane metody ewaluacji programów rozwoju zasobów ludzkich - Danilewicz, Dariusz (Modern of methods of evaluation of human resources development programs (choice), 2006)
Process of human resources measurement seems to be one of the main factor in building superiority over the rivals. It includes analysis of training programs efficiency. The article emphasizes the importance of improving the procedures of development programs evaluation, shows factors that influence the efficiency of human resources management and presents the brief description of the model of evaluation proposed by Jack J. Phillips. It also includes the results of the research on applying different methods of evaluation in the Polish practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 196-205